simplify (3x - 8) + (2x + 5) - (4x - 8)

1 answer

To simplify the expression \((3x - 8) + (2x + 5) - (4x - 8)\), follow these steps:

  1. Distribute the negative sign in front of the last parentheses: \[ (3x - 8) + (2x + 5) - 4x + 8 \]

  2. Now, combine like terms. Start with the \(x\) terms: \[ 3x + 2x - 4x = (3 + 2 - 4)x = 1x = x \]

  3. Next, combine the constant terms: \[ -8 + 5 + 8 = (-8 + 5 + 8) = 5 \]

  4. Putting it all together, the simplified expression is: \[ x + 5 \]

Thus, the final simplified result is: \[ \boxed{x + 5} \]

Similar Questions
  1. 1. Simplify 5^-1(3^-2)A. 45 B. 1/45 C. 15^-3 D. 15^2 2. Simplify (3xy^3)^2(xy)^6 A. 9x^8y^12 B. 3x^8y^12 C. 2x^3y^12 D. 9x^8y^9
    1. answers icon 7 answers
  2. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  3. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  4. Simplify 8a − 2a.Simplify 12e − 5f − 7e +3f. Simplify 9x + 3y − 6 − 5x + 4y −3. Simplify 9/11z − 4/11z. Simplify
    1. answers icon 4 answers
more similar questions